All-cancer incidence in Tehranian adults: more than a decade of follow-up—results from the Tehran Lipid and Glucose Study. (April 2020) - Hadaegh, F.; Asgari, S.; Hashemi, P.; Baghbani-Oskouei, A.; Eskandari, F.; Azizi, F.; Tohidi, M.
Abstract: Objectives: To investigate the incidence rates for different malignancies and assess the risk factors for all-cancer incidence in Tehran. Study design: Cohort study. Methods: This study consists of 8599 participants aged ≥ 30 years who were free of cancer (3935 men). Cancer diagnosis was based on pathology reports. Sex-stratified crude incidence rates and age-standardized incidence rates (ASRs) using Segi's method were calculated for all-cancers. Multivariate Poisson regression models were used to evaluate associations of potential risk factors, including sex, age, obesity status (body mass index [BMI]: 25–30 kg/m 2 as reference), education, smoking status, and diabetes mellitus with the incidence of cancers among the population. Incidence rate ratios (IRRs) with 95% confidence interval (CI) were also reported. Results: During a median follow-up of 13.9 years, there were 130 and 129 incident cancers for men and women, respectively; the corresponding ASRs were 356.1 and 243.6 per 100, 000 person-years, respectively. The three most incident cancers among men were gastrointestinal (GI) (ASR = 127.5), hematopoietic (ASR = 99.5), and reproductive system malignancies (ASR = 46.3). The most common incident cancers in women were breast cancer (ASR = 92.1), GI (ASR = 65.4), and reproductive system malignancies (ASR = 16.8). Among risk factors for cancer incidence, age (IRR [95% CI]: 1.05 [1.03–1.06]) and having a BMI < 25 kg/m 2 (IRR [95% CI]: 1.38 [1.01–1.90]) had a statistically significant association with incident cancer. Conclusions: The high rates of cancers in Tehran during more than a decade of follow-up calls for a need to define risk factors as well as to implement programs for early screening. Highlights: The age-standardized rate was 356.1 per 100, 000 person-years in men during 14 years. The age-standardized rate was 243.6 per 100, 000 person-years in women during 14 years. Gastrointestinal and hematopoietic were the two most incident cancers among men. Breast and gastrointestinal were the two most incident cancers among women.